Local budgeting in a budgetary decentralized context - Мykhailo Kuzheliev (Економічний вісник університету, 2018)
The subject of the study is the full range of methods for ensuring financial independence for local budgets in a decentralized environment. The purpose of the study is to work out a strategy based on the systematic approach to ensure financial independence for local budgets in a decentralized environment. The study methodology includes methods of analysis and synthesis, statistical methods, such as graphic and tabular methods, and methods for comparing and generalization. The results of the study. A comparative analysis of the impact of decentralization on the local budgeting has been carried out using the example of the 2014-2016 budget of Irpin. Some recommendation has been drafted to improve the system of local budgeting including some ways of greater development of the empowerment and autonomy of local budgets. Non-typical for Ukrainian economy gender method of budget analysis has been considered resulting in additional analysis of local budgets and eliciting a fact of the existence of some problematic budget lines regarding a gender-based approach in budgeting and working out a number of recommendation to eliminate them. The sphere of application of results. Local budgeting in a decentralized environment. Local budgets. Conclusion. Budget decentralization being taken into consideration opens up the prospect of the development of local self-government in order to deal effectively with the administration of local affairs, and enhance the role of citizens in the sphere of decision-making and practical implementation of socio-economic programs for the region. Financial basis of local budgets must assist local self-government in an effective implementation of the development strategy for the region. An analysis of the revenue and expenditure sides of the budget of Irpin in 2014-2016 in the context of the budgeting and income distribution of local budget shows a considerable increase in the level of fiscal decentralization of the income section of the budget, direct dependence of local authorities on the central Government and partly on transfer payments and emphasizes the need to strengthen the self-sustainability of local budgets and cover the requirement of financially literate managers. It has been found that a balanced division of powers between the central Government and the regions and decentralization of public finances are needed to reform local budgets (including the budget of Irpin). The sources of tax revenues are considered to be distributed between central and local authorities according to proper discharge of their duties that should be a subject for legislation on local self-government. Besides it is essentially necessary to give the local authorities the right to establish local taxes and duties and their rates. The analysis of a gender-based budgeting clearly indicates the importance of objective approach to budgetary expenditure. An integrated analysis of all the spheres of financing needs is important for rational and efficient allocation of financial resources at the state and local levels.